2021
DOI: 10.18502/ijaai.v20i1.5411
|View full text |Cite
|
Sign up to set email alerts
|

The Neutrophil-to-lymphocyte Ratio at the Time of Admission: A New Prognostic Indicator for Hospital Mortality of Trauma Patients

Abstract: The elevated neutrophil-to-lymphocyte ratio (NLR) is associated with poor clinical outcomes, especially in pro-inflammatory states such as surgical injuries and severe hemorrhages. Therefore, it was hypothesized whether NLR value at the time of admission could be a prognostic indicator of hospital mortality in trauma patients. This retrospective cohort study was conducted on 865 trauma patients referred to Rajaee Hospital between April 2016 and July 2019. The NLR value was calculated at the time of admission, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In our study, the NLR was lower in the RA‐TKA group than in the CM‐TKA group on the first postoperative day, and there was no difference between the two groups on the third or 30th postoperative day. Neutrophils rapidly increase in injured tissue in response to high concentrations of inflammatory mediators and damageassociated molecular patterns (DAMPs) 26 . It has also been shown that elevated NLR is a predictor of poor outcome following surgical injuries 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the NLR was lower in the RA‐TKA group than in the CM‐TKA group on the first postoperative day, and there was no difference between the two groups on the third or 30th postoperative day. Neutrophils rapidly increase in injured tissue in response to high concentrations of inflammatory mediators and damageassociated molecular patterns (DAMPs) 26 . It has also been shown that elevated NLR is a predictor of poor outcome following surgical injuries 23 .…”
Section: Discussionmentioning
confidence: 99%
“…These suggestions are supported by the elevation of these indexes in a number of conditions in and outside of the CNS, ranging from inflammatory, degenerative, malignant, vascular, and traumatic, in all of which index elevation correlates with poor prognosis [ 13 , 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The systemic immune response can be measured using hematological biomarkers, namely neutrophil to lymphocyte (NLR), thrombocyte/platelet to lymphocyte (PLR), and monocyte to lymphocyte ratios (MLR), which reflect an abnormal state of the immune response [ 9 - 12 ]. Variance in these parameters has been established to have prognostic significance in multiple conditions ranging from inflammatory and traumatic to cardiovascular and malignant [ 12 - 14 ]. Herein, we set out to establish the role of NLR, PLR, and MLR as prognostic markers for patient survival based on the newly defined WHO CNS 2021 criteria for GBM [ 13 - 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also observed that higher injury severity score was accompanied by high values of admission NLR, suggesting the straight association between the severity of the injury and intensity of next inflammatory response activation. 26 We proposed that high NLR values on patient arrival may be due to recruitment of neutrophils and macrophages, in the term of initial innate immune cells, to the site of injury and the need for neutrophil synthesis from the bone marrow (Figure 1(a)). 27,28 However, some researchers believed that lymphocytic anergy or loss occurred in trauma patients may be responsible for the elevation of NLR values.…”
Section: Main Textmentioning
confidence: 99%
“…44 However, our team achieved a cut-off value >5.27 for NLR upon the arrival of trauma patients. 26 These controversial values for NLR cut-off potentially stem from an unrecognized certain normal value of NLR. For instance, Forget et al evaluated the normal NLR values in healthy adults between 0.78 and 3.53.…”
Section: Main Textmentioning
confidence: 99%